Factorial series(!)

Calculus Level 4

S = 1 2 ! 1 ! 4 4 ! 3 ! + 16 6 ! 5 ! 64 8 ! 7 ! + S=\dfrac{1}{2!-1!} - \dfrac{4}{4!-3!} + \dfrac{16}{6!-5!} - \dfrac{64}{8!-7!} +\cdots

If S S above can be represented as 0 c sin a x b x d x \displaystyle \int_0 ^c \dfrac{ \sin ax}{bx} \, dx , where a , b , c a, b,c are positive integers, then enter the value of a + b + c a+b+c .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Rohith M.Athreya
Dec 27, 2016

0 c s i n a x b x d x \displaystyle \large \int_{0}^{c} \frac{sinax}{bx}dx is

1 b 0 a c s i n t t d t \displaystyle \large \frac{1}{b} \int_{0}^{ac} \frac{sint}{t}dt by putting a x = t ax=t

now making use of expansion for s i n x sinx ,

1 b 0 a c ( 1 t 2 3 ! + t 4 5 ! . . . ) d t \displaystyle \large \frac{1}{b} \int_{0}^{ac} (1-\frac{t^{2}}{3!}+\frac{t^{4}}{5!}-...)dt

this is 1 b [ a c ( a c ) 3 4 ! 3 ! + ( a c ) 5 6 ! 5 ! . . . ] \displaystyle \large \frac{1}{b} [ac-\frac{(ac)^{3}}{4!-3!}+\frac{(ac)^{5}}{6!-5!}-...]

the summation asked is 1 ( 1 ) n 1 2 2 n 1 2 ( 2 n 1 ) ( 2 n 1 ) ! \displaystyle \large \sum_{1}^{\infty} \frac{(-1)^{n-1}2^{2n-1}}{2(2n-1)(2n-1)!}

clearly, a c = 2 ; b = 2 \large ac=2 ; b=2

a + b + c = 5 \large {a+b+c=5}

Good solution.

Is the final form of the answer unique up to a c = 2 , b = 2 ac = 2, b = 2 ?

Calvin Lin Staff - 4 years, 5 months ago

Log in to reply

Thanks!

....

yes (as far as i can see currently)

Rohith M.Athreya - 4 years, 5 months ago
Chew-Seong Cheong
Dec 28, 2016

Note that:

S = 1 2 ! 1 ! 4 4 ! 3 ! + 16 6 ! 5 ! 64 8 ! 7 ! + . . . = 2 0 ( 2 1 ) 1 ! 2 2 ( 4 1 ) 3 ! + 2 4 ( 6 1 ) 5 ! 2 6 ( 8 1 ) 7 ! + . . . = 2 0 1 1 ! 2 2 3 3 ! + 2 4 5 5 ! 2 6 7 7 ! + . . . \begin{aligned} S & = \frac 1{2!-1!} - \frac 4{4!-3!} + \frac {16}{6!-5!} - \frac {64}{8!-7!} + ... \\ & = \frac {2^0}{(2-1)1!} - \frac {2^2}{(4-1)3!} + \frac {2^4}{(6-1)5!} - \frac {2^6}{(8-1)7!} + ... \\ & = \frac {2^0}{1 \cdot 1!} - \frac {2^2}{3 \cdot 3!} + \frac {2^4}{5 \cdot 5!} - \frac {2^6}{7 \cdot 7!} + ... \end{aligned}

Now consider:

sin x = x 1 ! x 3 3 ! + x 5 5 ! x 7 7 ! + . . . sin x x = 1 1 ! x 2 3 ! + x 4 5 ! x 6 7 ! + . . . sin x x d x = x 1 1 ! x 3 3 3 ! + x 5 5 5 ! x 7 7 7 ! + . . . 0 2 sin x x d x = 2 1 1 ! 2 3 3 3 ! + 2 5 5 5 ! 2 7 7 7 ! + . . . 0 2 sin x 2 x d x = 2 0 1 1 ! 2 2 3 3 ! + 2 4 5 5 ! 2 6 7 7 ! + . . . = S \begin{aligned} \sin x & = \frac x{1!} - \frac {x^3}{3!} + \frac {x^5}{5!} - \frac {x^7}{7!} + ... \\ \frac {\sin x}x & = \frac 1{1!} - \frac {x^2}{3!} + \frac {x^4}{5!} - \frac {x^6}{7!} + ... \\ \int \frac {\sin x}x dx & = \frac x{1 \cdot 1!} - \frac {x^3}{3 \cdot 3!} + \frac {x^5}{5 \cdot 5!} - \frac {x^7}{7 \cdot 7!} + ... \\ \int_0^2 \frac {\sin x}x dx & = \frac 2{1 \cdot 1!} - \frac {2^3}{3 \cdot 3!} + \frac {2^5}{5 \cdot 5!} - \frac {2^7}{7 \cdot 7!} + ... \\ \int_0^2 \frac {\sin x}{2x} dx & = \frac {2^0}{1 \cdot 1!} - \frac {2^2}{3 \cdot 3!} + \frac {2^4}{5 \cdot 5!} - \frac {2^6}{7 \cdot 7!} + ... = S \end{aligned}

a + b + c = 1 + 2 + 2 = 5 \implies a+b+c = 1+2+2 = \boxed{5}

Prakhar Bindal
Dec 27, 2016

By Maclaurin's series we have

sinx = x-x^3/3!+x^5/5!-x^7/7!

As we can see in the denominator of our series we have terms like 1 1! , 2 2!

So quite naturally we divide by x (so that on integration we get that)

sinx/x = 1-x^2/3!+x^4/5! ......

On integrating this we wont be able to get the required series . but if we replace x by 2x then

sin(2x)/2x = 1-4x^2/3!+16x^4/5!

Now just integrate this from 0 to 1 to get the required series

a = 2 b= 2 and c=1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...